High-Performance Microwave-Frequency Comb Generation Based on Directly Modulated Laser with Filtering Operations - Qianyou Long; Yang Jiang; Jing Xu; Xiaohong Lan; Jinjian Feng; Jiancheng Yu; Yunkun Luo; Tingyi Jiang; Hui Zhang; Yu Wu (Photonics)
In this paper, a scheme for generating high-quality tunable microwave-frequency combs (MFCs) is proposed. The proposed scheme is based on an initially non-flat MFC generated by a directly modulated laser operating in gain-switching status. Filtering operations are used to increase the flatness of the MFC. Concretely, by employing an optical bandpass filter and a two-tap negative-coefficient microwave photonic filter, the flatness of the MFC is significantly optimized. In the experiment, MFCs with adjustable comb spacing from 0.5 GHz to 1.6 GHz and bandwidths ranging from 0 to 26.5 GHz are generated. The flatness is better than ±2.5 dB for the MFC. The proposed scheme provides a simple, efficient, and high-performance solution for generating MFCs, making it a promising candidate for various applications requiring high-quality MFC sources.